Managing mixed Callitris-Eucalyptus forests for carbon and energy in central-eastern Australia. (September 2020) - Neumann, Mathias; Eastaugh, Chris; Adams, Mark
Abstract: Contributions of forests to meeting worldwide energy demand vary depending on management systems, growth conditions and legal and environmental constraints. Many countries rich in forest resources - including Australia - utilize those resources only sparingly owing to poor understanding of their sustainability. Semi-arid woodlands dominated by Callitris and Eucalyptus spp. are common in inland Australia but are slow growing. There is little published information on wood properties (including basic density, carbon concentration, energy) for this forest type. We estimated the carbon and energy stocks of mixed Callitris stands in central-eastern Australia, linking laboratory analysis with field sampling and surveys. Wood density of Callitris spp. was 30% less than that of admixed Eucalyptus spp. Carbon and energy densities of Callitris spp. were also less than admixed species, albeit with reduced variation. While Eucalyptus spp. constitute about 40% of the growing stock, and have mostly larger dimensions, they are not generally harvested due to regulatory constraints and limited markets for their wood products. Based on conservative rates of growth, harvested biomass would provide 4000 kWh ha −1 year −1 . If used with cogeneration technology, biomass fuel could assist in balancing seasonal energy demands, especially for heating and cooling. While slow-growing, Callitris-Eucalyptus forests share many features with other economically relevant species and forests worldwide. Quantification of potential bioenergy is a crucial first step in optimizing forest management and addressing the market constraints and infrastructure needs of any potential biofuel project. Graphical abstract: Image 1 Highlights: We quantify carbon and energy of a widespread, poorly known native Australian conifer. These Callitris-Eucalypt forests contain more energy per volume than temperate forests. Thinning a 1100 ha forest every 6 years can cover 20% of energy demand of nearby city. The energy in the annual growth of 1 ha equals the heating demand of 6 persons.